The Ovarian Development Genes of Bisexual and Parthenogenetic Haemaphysalis longicornis Evaluated by Transcriptomics and Proteomics - Wang, Tianhong; Wang, Tongxuan; Zhang, Meng; Shi, Xinyue; Zhang, Miao; Wang, Hui; Yang, Xiaolong; Yu, Zhijun; Liu, Jingze (Frontiers in Veterinary Science, 2021)
The tick Haemaphysalis longicornis has two reproductive groups: a bisexual group (HLBP) and a parthenogenetic group (HLPP). The comparative molecular regulation of ovarian development in these two groups is unexplored. We conducted transcriptome sequencing and quantitative proteomics on the ovaries of HLBP and HLPP, in different feeding stages, to evaluate the molecular function of genes associated with ovarian development. The ovarian tissues of HLBP and HLPP were divided into three feeding stages (early-fed, partially-fed and engorged). A total of 87,233 genes and 2,833 proteins were annotated in the ovary of H. longicornis in the different feeding stages. The differentially expressed genes (DEGs) of functional pathway analysis indicated that Lysosome, MAPK Signaling Pathway, Phagosome, Regulation of Actin Cytoskeleton, Endocytosis, Apoptosis, Insulin Signaling Pathway, Oxidative Phosphorylation, and Sphingolipid Metabolism were most abundant in the ovary of H. longicornis in the different feeding stages. Comparing the DEGs between HLBP and HLPP revealed that the ABC Transporter, PI3K-Akt Signaling Pathway and cAMP Signaling Pathway were the most enriched and suggested that the functions of signal transduction mechanisms may have changed during ovarian development. The functions of the annotated proteome of ovarian tissues were strongly correlated with the transcriptome annotation results, and these were further validated using quantitative polymerase chain reaction (qPCR). In the HLBP, the expression of cathepsin L, secreted proteins and glycosidase proteins was significantly up-regulated during feeding stages. In the HLPP, the lysozyme, yolk proteins, heat shock protein, glutathione S transferase, myosin and ATP synthase proteins were up-regulated during feeding stages. The significant differences of the gene expression between HLBP and HLPP indicated that variations in the genetic background and molecular function might exist in the two groups. These results provide a foundation for understanding the molecular mechanism and exploring the functions of genes in the ovarian development of different reproductive groups of H. longicornis.